Analysis of the Application of Waqf Core Principle in Risk Management Case Study: the Waqf Maintenance and Development Foundation of Pondok Modern Darussalam Gontor - Rahayu Zarhana; Roghiebah Jadwa Faradisi (Al-Awqaf: Jurnal Wakaf dan Ekonomi Islam, 2022)
Abstract: This research was conducted to find out the factors that inhibit performance or work performance in the application of Waqf Core Principles in risk management at the Waqf Maintenance and Development Foundation of Pondok Modern Darussalam Gontor. This research uses qualitative research methods and descriptive approaches. The data collection technique used is triangulation which combines information from various data collection techniques and existing data sources. The results of this study showed that the risk factors that is identified to be possible risk are consisted of internal and external factors of the foundation. The application of Waqf Core Principles in risk management, consists of risk management, collection management, counterparty risk, disbursement management, problem waqf assets, provisions, and reserves, transactions with related parties, country and transfer risks, market risk, reputation and waqf asset loss risk, revenue/profit-loss sharing risk, disbursement risk, operational risk and shari’ah-compliant. Two of these regulatios, are counterparty risk, and country and transfer risks are not applicable to the foundation. The counterparty risk has not been applied because cash waqf has never occurred at the Waqf Maintenance and Development Foundation of Pondok Modern, The country and transfer risks due to the absence of assets involving two countries. Keywords: Risk Management, Waqf Core Principles, Waqf.